-10x-2=11-9x

Simple and best practice solution for -10x-2=11-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10x-2=11-9x equation:



-10x-2=11-9x
We move all terms to the left:
-10x-2-(11-9x)=0
We add all the numbers together, and all the variables
-10x-(-9x+11)-2=0
We get rid of parentheses
-10x+9x-11-2=0
We add all the numbers together, and all the variables
-1x-13=0
We move all terms containing x to the left, all other terms to the right
-x=13
x=13/-1
x=-13

See similar equations:

| x^-x=6 | | 139-(3x+14)=2x | | 2/3x+15=20-x | | 3.2x+9=5.7x | | 2q–4=26 | | 11/4+21/2=w | | b/4=12.75 | | 31/3=3/10w | | 2+3n=4/5n+12 | | A-7=-a+1 | | 4.2k=14.7 | | x^2-x-10=7x-1 | | (x+6)+x=86 | | -10=2(b-4) | | -4.5w=-25/3 | | 3x=-5^2+25 | | x^2+x+26=-9x+2 | | 139-2x=3x+14 | | 3.14s=81.2004 | | 12-x|2+3=1 | | 45/45=5n/54 | | 3/2h=5/2 | | 3x-8=5x+13 | | x^2-24x+0=0 | | -3+7n=1+8n | | −2x=34 | | x+x/3=1 | | 846+t=-538 | | 7p-7=0 | | (2n-5)=-90 | | 8n=-5+-3 | | 6x+x+16+3x-1+5x=180 |

Equations solver categories